Implementasi Konsep Pendidikan Ki Hajar Dewantara di SMP Negeri 1 Bitung - Maritje Maria Makalew; Paulus Joseph Mentang (ECCE: Jurnal Pendidikan Pastoral Kateketik, 2023)
The focus of this research is the Implementation of the Ki Hajar Dewantara Education Concept at SMP Negeri 1 Bitung. This research uses descriptive research methods with a qualitative approach. Data collection techniques used in qualitative research are observation, interviews, and documentation. The conclusion of the study is, first: in the Application of the Ki Hajar Dewantara Education Concept at SMP Negeri 1 Bitung. The implementation itself has begun to be implemented and the application includes three environments, namely, the family environment, the school environment, and the community environment. Second: what are the supporting factors and inhibiting factors in the Ki Hajar Dewantara Education Concept, namely the support of teachers in building enthusiasm and intentions for students, then there is support from parents and the environment in developing their talents and potential. Meanwhile, the inhibiting factors themselves lack the creativity of subject teachers when studying online, inadequate study hours, and lack of intense communication between teachers and students. And then the third: efforts in improving the Ki Hajar Dewantara Education Concept at SMP Negeri 1 Bitung, namely, subject teachers make creative and innovative activity plans by considering all aspects as well as possible. Then the teacher reflects and evaluates at the end of the class hour to achieve the learning objectives.